Diagnostic Accuracy and Validity of Magnetic Resonance Imaging in the Detection of Speci!c Type of Brain Tumour (Bangladesh Medical Journal, 2019)
Magnetic Resonance Imaging (MRI) is a widely accessible imaging technique for the detection of brain tumours and cancer, which are further confirmed by histopathological examination. Accurate detection of the tumours and its extent is very difficult. The present study attempted to evaluate the convenience of MRI in detection of different grades of astrocytomas, which are the most commonly occurring brain tumours. This cross-sectional study was conducted at the Department of Radiology and Imaging with the collaboration of Department of Neurosurgery and Department of Pathology at Sir Salimullah Medical College (SSMC & MH), Dhaka from January 2013 to December 2013 for a period of one year. The study population was all the diagnosed cases of intracranial astrocytoma patients regardless of their age and sex. The studied included 48 brain tumour (astrocytoma) patients, ages between 13 and 69 years old. All cases having no contraindication for MRI underwent MR examination followed by histopathological examination of the postoperative resected tissues. The findings of the MRI and histopathological examination were compared to find out the test validity of the MRI findings of the different grades of astrocytoma’s. The highest sensitivity was found in grade III astrocytoma (90.5%) followed by grade II (85.7%) grade IV (75.0%) and grade I (60.0%). The highest specificity was found in grade I astrocytoma (97.7%) followed by Grade III (96.3%), grade IV (92.5%) and grade II (91.5%). The highest accuracy was found in both grade I astrocytoma (93.7%) and grade III (93.7%) followed by grade II (92.5%) and grade IV (89.6%). As per the study findings it can be concluded that,MRI has a high diagnostic accuracy and validity for the detection of different grades of astrocytoma.Bangladesh Med J. 2017 Sep; 46 (3): 85-89